JUMLAH STOMATA DAN KLOFIL DAUN PADA 3 AKSESI TANAMAN PEGAGAN TERHADAP INTENSITAS PENYIRAMAN - wulandari, siti; Nurhayati, Nurhayati; Yunus, Ahmad; Pardono, Pardono; Widyastuti, Yuli (Innofarm : Jurnal Inovasi Petanian, 2025)
Pegagan is a plant that is widely used for its leaves. The surface of pegagan leaves has stomata that function to regulate gas exchange and transpiration. In addition to the number of stomata, chlorophyll content also greatly affects photosynthesis. Chlorophyll helps plants absorb sunlight during photosynthesis, converting CO2 into carbohydrates for plant energy. This study aims to obtain accessions that are resistant to environmental stress and have high chlorophyll content, as well as to obtain appropriate watering applications. This study was conducted from May to September 2019. The research was conducted in two locations, namely the Jumantono Experimental Laboratory (pegagan cultivation) and the Laboratory of Physiology and Tissue Culture, Faculty of Agriculture, Sebelas Maret University for laboratory analysis. The tools used were polybags, soil, manure, 3 pegagan seed accessions, nail polish, microscope slides, and a UV-Vis spectrophotometer. The field study employed a completely randomized design (CRD) with two factors: factor 1 was accession (accession 1, accession 2, accession 3), and factor 2 was watering intensity (once a day, every two days, every three days), with three replications. The research results and observation data were analyzed using Analysis of Variance, and if significant differences were found, they were followed by Duncan's Multiple Range Test (DMRT) at 5%. Watering intensity did not affect the number of stomata or the width of stomata, stomatal width and leaf chlorophyll in C. asiatica. Accessions with the highest number of  stomata and high chlorophyll content were accession 1. Keywords: Tempeh Liquid Waste, Peanut Plant Litter, Soybean Seeds